2014
DOI: 10.1177/105268461402400504
|View full text |Cite
|
Sign up to set email alerts
|

Parent Social Networks and Parent Responsibility: Implications for School Leadership

Abstract: Family–school partnerships are difficult to initiate and sustain in ways that actually promote student learning, especially in high-poverty communities. This quantitative study was designed to better understand how social forces shape parent responsibility in education. Based on social cognitive theory as the conceptual framework, the relationships between parent responsibility and two types of parent social networks were tested according to a partially latent structural equation model. Findings indicate limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…For example, as parents see other parents model involvement behavior, they are more likely to internalize those same actions and persevere through obstacles and difficulties. Empirical evidence to justify this claim comes from Sheldon (2002) and Curry and Adams (2014). Each found a positive relationship between the size of parents’ social networks and parent involvement.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, as parents see other parents model involvement behavior, they are more likely to internalize those same actions and persevere through obstacles and difficulties. Empirical evidence to justify this claim comes from Sheldon (2002) and Curry and Adams (2014). Each found a positive relationship between the size of parents’ social networks and parent involvement.…”
Section: Methodsmentioning
confidence: 99%
“…As social network theory suggests, investment in various forms of parental empowerment such as explicit positive interactions between parents, especially interaction between less involved parents and highly involved parents, can enable parents to gain a better understanding of how to exert influence over the education of their children (Lin, 2001). In support of this application of social network theory, recent research indicates that size of parent social network (Curry & Adams, 2014; Sheldon, 2002) and that frequency of contact and importance of relationships between parents (Curry & Adams, 2014) are positively related to parent involvement in their child’s education.…”
Section: Conceptual Frameworkmentioning
confidence: 96%
“…Purposeful sampling was used. This qualitative study is a follow up of a 2010 study that identified six schools in this district as having higher parent role construction, parent efficacy, and stronger connections between parents within the school as compared with other schools in this district (Curry & Adams, 2014). The district is the second largest district in this Midwestern State with a student population of 40,111 in the fall of 2014.…”
Section: Methodsmentioning
confidence: 99%
“…Sheldon (2002) and Curry and Adams (2014) find statistically significant, positive relationships between the size of parent social networks and parent choice for involvement. These findings suggest that relationships among parents in the school may be an important factor in determining the actions that parents take to fulfill their roles in the educational process and in their efficacy to fulfill their roles.…”
Section: Introductionmentioning
confidence: 93%
“…Indeed, many studies explored the social causes behind (a lack of) coproduction and referred to Bourdieu's notion of social capital (e.g. Curry and Adams, 2014;Shoji et al, 2014). They questioned teachers' notions about parent involvement, poverty issues and disadvantaged groups (Frempong et al, 2011) and discussed the implications of the different resources parents could make available to their children.…”
Section: Empirical Papersmentioning
confidence: 99%